Analysis of the Influence of Service Quality, Store Atmosphere, Visual Merchandising on Interest and Repeat Purchases - Khuluq, Muhamad Khusnul; Safirin, Moch. Tutuk (Journal La Sociale, 2024)
In the world of the culinary industry, competition in the restaurant business is increasingly fierce. Wizzmie must continue to provide the best offers for consumers. People's buying interest in visiting restaurants is not only because of the delicious taste of food and drinks, but also because of the quality of service, comfortable atmosphere and attractive product sales. Researchers are interested in knowing the influence of Service Quality, Store Atmosphere and Visual Merchandising variables on consumer interest and repeat purchases at Wizzmie Rungkut branch. The focus of this research is customers of the Rungkut branch of Wizzmie Restaurant with 110 respondents using the purposive sampling method. Research data was obtained from distributing questionnaires using a Likert scale. The research results show that the Purchase Interest variable has a moderate influence on the dependent variable at 49%, as well as the Repeat Purchase variable at 44.7%. The GoF test result of 0.553 shows that the entire SEM-PLS model is in the high suitability category, so that the data is able to explain the relationship between the variables studied. The variables Service Quality and Visual Merchandising have a significant effect on Purchase Interest, and Purchase Interest has a significant influence on Repeat Purchases, while Store atmosphere has no influence on Purchase Interest.